How to design and evaluate research in education - Fraenkel, Jack R.; Wallen. Norman E. (Boston, 2006)
An introduction to educational research, this text covers the research methodologies and discusses the research process. It presents an analysis of real research studies which provides students with examples of how to prepare their work and read that of others.
Keywords: Education Research Evaluation; Education Research Methodology